KEEFEKTIFAN MEDIA KOMUNIKASI VISUAL SEBAGAI PENUNJANG PROMOSI PADA PERGURUAN TINGGI RAHARJA - Lusyani Sunarya; Po Abas Sunarya; Jasmine Dara Assyifa (CCIT Journal, 2015)
The development of visual communication media at this time is very helpful in supporting information and communication. But often presented visual communication media are less effective and appropriate. While so many universities in Indonesia, the increasingly fierce competition in attracting new students. Media Visual Communication can be applied to college in introducing or raising the image and popularity or promote and provide information to prospective students. In essence, in this case the effectiveness of media campaigns assessed in spreading information, influence or persuade prospective students and new student to join the university. The method used by the questionnaires to assess the effectiveness of implemented that have been implemented such as brochures, banners, posters, billboards, catalogs, paper bag, flyers and merchandise. In conclusion, this article specifically assess visual communication media from case studies in Perguruan Tinggi Raharja considered effective and consistent contribution.. This study found a great opportunity to improve the promotion of additional digital marketing media campaign called the college through the stages resulting in some visual communication media that can be received by the target audience. To create a media campaign needs planning in accordance with the background of the problem so that the media are made to overcome the problems encountered